The Relationship between Translated Fairy Tales and Oral Narrative Tradition: Charles Perrault’s Contes in Georgian Folklore - Gogiashvili, Elene (Translation Studies: Theory and Practice, 2023)
What does put Little Red Riding Hood in her basket when she arrived in Georgia? What was the name of that demonic antagonist who met Little Thumb? An overview of archival sources gives an account of characteristics of Georgian folkloric adaptations of Charles Perrault's fairy tales. The paper deals with transmissions between the categories of "oral" and "literary", and relations between translated print products and oral narratives. The comparison of literary and folkloric versions of fairy tales shows certain features that are universal and serve as a medium between the literature and oral narrative traditions.
Keywords: folktales; fairy tales; Little Red Riding Hood; Little Thumb; Georgia